2023
DOI: 10.1007/s11440-023-01896-3
|View full text |Cite
|
Sign up to set email alerts
|

Static and cyclic performance of polyurethane foam adhesive bound soil–rubber mixtures under drained conditions

Abstract: The major drawbacks of a railway track include noise, vibration, and aggravated track degradation. Resilient mats and asphalt have been increasingly used in recent years to mitigate this noise and vibration. However, these materials are quite expensive. Conventional asphalt is very stiff and brittle, making it more prone to cracking. The present work aims to develop a novel material that can be used as a base layer in ballasted and slab tracks. The current research proposes a sustainable and resilient base cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…The two soil types are classified as well-graded gravel (GW) and well-graded sand (SW), following the ASTM D2487 standard [41]. More details on the material description can be found elsewhere [24,42,43].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The two soil types are classified as well-graded gravel (GW) and well-graded sand (SW), following the ASTM D2487 standard [41]. More details on the material description can be found elsewhere [24,42,43].…”
Section: Methodsmentioning
confidence: 99%
“…The two soil types are classified as well-graded gravel (GW) and well-graded sand (SW), following the ASTM D2487 standard [41]. More details on the material description can be found elsewhere [24,42,43]. Static direct simple shear (SDSS) tests were conducted using a direct simple shear apparatus (Figure 4a) to determine the optimum dosage of scrap rubber granules and PFA.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies [19,47] report reduced settlement, while others [14] observed an increase in settlement due to scrap rubber addition. Recently, a rigorous laboratory investigation was performed by Farooq and Nimbalkar [15] to investigate the influence of scrap rubber on the performance of granular soil. They observed that at low rubber content (5-10%), a reduction in the settlement is observed, while the settlement increases at higher rubber dosages.…”
Section: Introductionmentioning
confidence: 99%